Female Clients Satisfaction towards Primary and Secondary Eye Health Facilities and Cost of Eye Care in Nepal - Upreti Oli, Radhika; Poudel, Manish; Hazel, Yadira Perez; Manandhar, Anu; Shrestha, Mohan Krishna; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2021)
Introduction: In Nepal, females suffer from disproportionately higher burden of blindness and vision impairment with low access to eye care. The available knowledge is inadequate to address the issues related to gender and generate information to reduce the gender disparity. The aim of this study was to determine female clients’ satisfaction with services at eye facilities in Nepal and to estimate the cost of cataract surgery. Materials and methods: Exit interviews were conducted in 2018 with 308 female clients from eight facilities in five districts. Face to face interviews were conducted using a pretested semi-structured questionnaire adopted from the midterm review of Vision 2020. Results: The mean age of participants was 54±17 years. Ninety seven percent (97%) of the participants reported that they received service as per their expectation and were satisfied with the service of the facilities. Major factors for satisfaction were: thorough eye examination (54%), behavior of health staff (40%), and cleanliness of health facility (39%). Another eighty percent (80%) of the participants mentioned that they would recommend or return to the same facility. Fifteen percent of the participants perceived that they faced problems at the eye facility because of their gender. Around three quarters (73%) paid health expenses from their pocket. Most (83%) of the participants rated user fees as either reasonable or inexpensive. Conclusion: The majority of participants reported receiving service as expected and willingness to return to the same eye health facility for future consultation. However, most participants had to pay the health care expenses out-of-pocket.